Computer gaming and its influence on critical thinking skills and academic performance - Castell, Christian Zuniga (2007)
The study examined the relationship between critical thinking skill, academic performance, and the amount of time male students play computer games. A Critical Thinking Test and Gamer Profile form were used to gather the necessary information from 128 fourth year male students from two high schools in Metro Manila. The data were analyzed using descriptive statistics, Pearson's correlation, and a multiple regression. The results of the study reveals that the critical thinking skills of high school students are below the desired level of competency as they barely passed the Critical Thinking Test. Looking at the computer gaming practices, almost all of the respondents play computer games in addition to their other activities. They only vary in terms of the amount of time allotted and the computer games they played. The computer games that the students play have little academic value and contribution to the development of critical thinking skills. To examine the factors that influence critical thinking, a regression model was created where academic achievement and computer gaming time were used as predictors. It turned out that academic achievement can significantly explain critical thinking skills. When computer gaming time was added as a predictor along with academic achievement, the explanatory power of the model increased but with very negligible amount. This study recommends that parents must intervene in the allocation of time their children have for playing computer games and the kind of computer games that they play. In schools, there should be a serious consideration in the effective integration of critical thinking skills in school curriculum. Lastly, the study recommends that the game developers and gaming companies promote corporate social responsibility through the development and popularization of computer games with academic context and those that can promote critical thinking.